2005
DOI: 10.1049/el:20057147
|View full text |Cite
|
Sign up to set email alerts
|

Rate-distortion estimation for fast JPEG2000 compression at low bit-rates

Abstract: In JPEG2000 block coding, all coding passes are generated before rate allocation is performed among code-blocks. Unwanted passes are then discarded. For low bit-rate coding, this results in discarding of a large number of coding passes. In this letter, we propose a rate-distortion estimation method that enables pre-compression rate-distortion optimization to be carried out, wherein only the required passes need to be coded. Experiments using the proposed technique demonstrate speedup factors ranging from 1.17 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 8 publications
(6 reference statements)
1
16
0
Order By: Relevance
“…With the aim to reduce the computational load of the tier-1 coding stage when applying the PCRD method, more than 26 different ratedistortion optimization methods have been proposed in the last five years. Some of them are [6,7,8,9,10,11,12] (an extensive review and comparison among several methods can be found in [1]).…”
Section: Rate-distortion Optimizationmentioning
confidence: 99%
See 2 more Smart Citations
“…With the aim to reduce the computational load of the tier-1 coding stage when applying the PCRD method, more than 26 different ratedistortion optimization methods have been proposed in the last five years. Some of them are [6,7,8,9,10,11,12] (an extensive review and comparison among several methods can be found in [1]).…”
Section: Rate-distortion Optimizationmentioning
confidence: 99%
“…Therefore, the rate control method should concatenate the coding pass MRP of a code-block with the following CP. We explain this characteristic using the rate-distortion model from [9], which estimates the decrement in distortion and the increment in bit-rate of a code-block at the bit-plane p according to…”
Section: Characterization Of the Rate-distortion Slopementioning
confidence: 99%
See 1 more Smart Citation
“…In literature, there are several proposal of approaches that modify only the coder (thus preserving the standard compatibility [14][15][16][17][18][19][20][21][22][23][24][25][26]) or both the coder and the decoder. Our approach belongs to the second group and the gain over the standard will be motivated from a theoretical point of view (by definition of a gain function, see Section 4.2) and by the experimental results.…”
Section: Introductionmentioning
confidence: 99%
“…There is still much improvement space for JPEG2000 due to its open architecture. The optimality of context quantization of context-adaptive arithmetic coding is explored in [3,4]; [5,6] are absorbed in the speed-up of the bitplane coding (Tier1 coding) and optimized truncation (Tier2 coding) in JPEG2000.…”
Section: Introductionmentioning
confidence: 99%